Rehabilitation of Executive Functions in a Real-Life Setting: Goal Management Training Applied to a Person with Schizophrenia - Levaux, M.-N.; Larøi, F.; Malmedier, M.; Offerlin-Meyer, I.; Danion, J.-M.; Van der Linden, M. (Case Reports in Psychiatry, 2012)
The aim was to assess the efficacy of a modified version of Goal Management Training (GMT) in a person with schizophrenia who had difficulties in attaining the final goal for new and multitasking daily-life situations. GMT is designed to improve abilities in establishing goal-directed plans and carrying them out effectively. Beneficial effects of GMT were measured for several clinical questionnaires, laboratory tasks, and three real-life situations: meal preparation (trained, familiar); washing (nontrained, familiar); meeting preparation (nontrained, unfamiliar). The results revealed improvement in planning and on trained laboratory and meal preparation tasks and a generalization of GMT effects on nontrained laboratory and everyday tasks. Self-esteem also improved. Finally, a two-year followup indicated the durability of the beneficial effects.